Leveraging Collaboration and Peer Support to Initiate and Sustain a Faculty Development Program - Anneris Coria-Navia; Scott Moncrieff (To Improve the Academy)
In today’s impoverished higher education fiscal climate, especially considering the enormous financial implications to higher education of accommodating the changes required by the coronavirus pandemic, “nonessential” though highly important programs, such as centers for teaching and learning (CTLs), are very likely to be underfunded. In this study, we illustrate how underfunded programs can leverage peer collaboration and support to initiate productive, formal systems of assistance for faculty by describing a number of such programs developed by and/or coordinated by our CTL. Moreover, we propose that sustainable programs, especially at small liberal arts institutions, must include a strong component of peer networking and in-house expertise rather than relying on outside consulting services. In a climate of shrinking dollars, CTLs can still perform some key roles effectively while continuing to advocate for more adequate funding.